2007
DOI: 10.1165/rcmb.2006-0133oc
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial Cell Apoptosis by Fas Ligand–Positive Myofibroblasts in Lung Fibrosis

Abstract: The Fas/Fas ligand (FasL) apoptotic pathway has been shown to be involved in bleomycin-induced lung fibrosis. We examined the hypothesis that myofibroblasts from fibrotic lungs possess a cytotoxic phenotype that causes apoptosis of epithelial cells via the Fas/FasL pathway. We show in vivo epithelial cell apoptosis and associated upregulation of Fas and apoptotic Fas pathway genes in epithelial cells of lungs with bleomycin-induced fibrosis. In addition, we show that FasL surface molecules are overexpressed on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
100
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(104 citation statements)
references
References 30 publications
3
100
1
Order By: Relevance
“…The current authors have recently confirmed that bleomycin causes apoptosis of lung epithelial cells in vitro in a time-and dose-dependent manner [10], and also reported the specific induction of epithelial cell apoptosis by myofibroblasts from fibrotic lungs via the Fas/Fas ligand pathway [11]. The aim of the present study was to evaluate telomerase activity in bleomycintreated lung epithelial cells (LECs) and the resulting effect on apoptosis in bleomycin-treated mouse lung epithelial (MLE) cells.…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…The current authors have recently confirmed that bleomycin causes apoptosis of lung epithelial cells in vitro in a time-and dose-dependent manner [10], and also reported the specific induction of epithelial cell apoptosis by myofibroblasts from fibrotic lungs via the Fas/Fas ligand pathway [11]. The aim of the present study was to evaluate telomerase activity in bleomycintreated lung epithelial cells (LECs) and the resulting effect on apoptosis in bleomycin-treated mouse lung epithelial (MLE) cells.…”
mentioning
confidence: 66%
“…It was also demonstrated that they induce apoptosis of lung epithelial cells in vivo, a possible mechanism for the prevention of lung tissue remodelling [11]. Apoptosis thus plays a role in the induction of fibrosis.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Two recent studies have shown a similar sensitizing effect of PGE 2 on Fas-induced fibroblast apoptosis (14,21). Although the source(s) of Fas ligand (FasL) are not completely known, recent studies have suggested that myofibroblasts themselves may be an important source in the fibrotic lung (22,23). Taken together, these findings suggest that fibroblast and myofibroblast accumulation in the lungs of IPF patients could occur as a result of impaired sensitization to Fas-induced apoptosis.…”
mentioning
confidence: 93%